Enhancing Early Literacy: The Effectiveness of the Picture Word Inductive Model with Smartphone Assistance in the Early Childhood to Elementary Transition - Asep Deni Gustiana; Heny Djoehaeny; Mubiar Agustin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Bridging the learning gap between Early Childhood Education (ECE) and Elementary School (ES) requires an effective transition program. An adaptive learning strategy is crucial to accommodate diverse student profiles and preparation levels. This study examines the effectiveness of the Picture Word Inductive Model with Smartphone Assistance (PWIMSA) in enhancing literacy skills during the ECE-ES transition. A quasi-experimental pretest-posttest control-group design was employed without randomization. The study involved 203 first-grade students from five elementary schools in Bandung, selected through purposive sampling. The schools were chosen based on their adoption of the autonomous curriculum and piloting of the ECE-ES transition program. The experimental group (n = 93) received instruction using the PWIMSA approach, while the control group (n = 110) participated in the school literacy movement program. An independent t-test analysis of gain scores revealed a significant difference in literacy skill improvement between the experimental and control groups (significance value α). The experimental group demonstrated an average gain of 6.92 points higher than the control group, indicating that PWIMSA is more effective in enhancing foundational reading skills. The findings suggest that PWIMSA supports literacy development by accommodating diverse student abilities and learning needs. Its integration into transition programs can bridge early education gaps and foster stronger literacy foundations. PWIMSA is an effective instructional approach for improving literacy skills in the ECE-ES transition program, addressing student diversity and enhancing foundational reading abilities.